Does quercetin affect tendon healing? An experimental study in a rat model of Achilles tendon injury - Ahmet Yurteri; Numan Mercan; Zeliha Esin Çelik; Hakan Yaykaşlı; Ahmet Yıldırım (Frontiers in Medicine)
PurposeThe objective of this study was to investigate the impact of quercetin, a potent antioxidant, on tendon healing utilizing a rat Achilles tendon injury model.Materials and methodsThe study involved 32 male Wistar-Albino rats, randomly split into experimental (quercetin) and control groups, each with 16 rats. A bilateral Achilles tenotomy model was applied, with the experimental group receiving quercetin and the control group receiving corn oil via oral gavage from surgery until sacrifice. One Achilles tendon per rat underwent histopathological and immunohistochemical evaluations, while the other underwent biomechanical analysis.ResultsTendons were evaluated histopathologically in terms of tenocyte, ground substance, collagen, and vascularity, and quercetin was observed to significantly increase tendon healing in the experimental group (p-values = 0.0232, 0.0128, 0.0272, 0.0307, respectively). In the immunohistochemical analysis, type I collagen, type III collagen, alpha smooth muscle actin (SMA), and Galectin-3 were evaluated, and it was observed that quercetin increased tendon healing (p-values = 0.0166, 0.0036, 0.0323, 0.0295, respectively). In the biomechanical analysis, the rupture strength was evaluated with six parameters (failure load, maximum energy, displacement, stiffness, ultimate stress, and strain), and it was observed that quercetin significantly increased the rupture strength (p-values = 0.032, 0.014, 0.026, 0.025, 0.045, 0.012, respectively).ConclusionQuercetin significantly enhanced tendon healing both biomechanically and immunohistochemically. However, further clinical studies are needed to understand its effects on human tendon healing, as this is the first study of its kind.